2012
DOI: 10.1117/12.913556
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic origins of the surface exciton photoluminescence in ZnO nanostructures

Abstract: Photoluminescence (PL) studies of the surface exciton peak in ZnO nanostructures at ∼3.367 eV are reported to elucidate the nature and origin of the emission and its relationship to nanostructure morphology. Localised voltage application in high vacuum and different gas atmospheres show a consistent PL variation (and recovery), allowing an association of the PL to a bound excitonic transition at the ZnO surface modified by an adsorbate. Studies of samples treated by plasma and of samples exposed to UV light un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In this context, photoluminescence (PL) spectroscopy is known to be a very sensitive and powerful technique to track the existence of defects in metal oxides like AZO and TiO2, and to understand the nature of sub-band gap states generated either by perturbing the crystal structure, 17 doping with foreign elements, 18,19 or by directly introducing Vo and/or interstitials in the matrix. [20][21][22] For example, Lin et al reported an intense blue and green, and faint yelloworange luminescence band in ZnO nanostructures, and attributed this in the light of deep level defects, 20 particularly Zni, ionized Vo (𝑉 𝑜 + /𝑉 𝑜 ++ ) and oxygen interstitials (Oi).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, photoluminescence (PL) spectroscopy is known to be a very sensitive and powerful technique to track the existence of defects in metal oxides like AZO and TiO2, and to understand the nature of sub-band gap states generated either by perturbing the crystal structure, 17 doping with foreign elements, 18,19 or by directly introducing Vo and/or interstitials in the matrix. [20][21][22] For example, Lin et al reported an intense blue and green, and faint yelloworange luminescence band in ZnO nanostructures, and attributed this in the light of deep level defects, 20 particularly Zni, ionized Vo (𝑉 𝑜 + /𝑉 𝑜 ++ ) and oxygen interstitials (Oi).…”
Section: Introductionmentioning
confidence: 99%